Performance analysis of CMOS-memristor hybrid ring oscillator Physically Unclonable Function (RO-PUF) - Loong J.T.H.; Hashim N.A.N.; Hamid M.S.; Hamid F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
CMOS integrated circuits; Hardware; Memristors; Reconfigurable hardware; Aliasing; Memristor; Physically unclonable functions; Ring oscillator; uniformity; uniqueness; Hardware security